Designing Home-Based Childcare Program for Stimulating Social-Emotional Development in Early Childhood - Wahyuni, Fitri Ayu; Rinekasari, Nenden Rani; Jubaedah, Yoyoh; Boonsong, Sutthiporn (Indonesian Journal of Multidiciplinary Research, 2021)
The program for social-emotional development stimulation is an essential aspect in early childhood in childcare. The childcare environment at home and every child's individual needs was the attention of this study. The method used a design-based research model that is covering the planning, production, and evaluation. Technique data collection for this research used interviews and validation expert judgment. These research participants are the early childhood education expert, family education expert, and practitioner’s childcare. The validation proceeds at stage 1 indicate that the program in the category worthy of revision. In phase 2, the program created is highly feasible. Therefore, childcare could use the program to stimulate social-emotional development for early childhood. The research was recommended to the childcare maintainer that the home-based childcare program could be used as a guide in childcare and for the next researcher to research the implementation of home-based childcare programs.